The effects of gas phase on the protein conformation a molecular dynamics study on Eotaxin-3 Cytokine - Ahmad Khairudin, N. B.; Wahab, H. A.; Samian, M. R.; Najimudin, N. (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
In the current work, the structure of the enzyme CC chemokine eotaxin-3 (IG2S) was chosen as a case study to investigate the effects of gas phase on the protein conformation using molecular dynamics simulation. Generally, simulating proteins in the gas phase tend to suffer from various drawbacks, among which excessive numbers of proteinprotein hydrogen bonds. However, current results showed that the effects of gas phase simulation on IG2S did not amplify the protein-protein hydrogen bonds. It was also found that some of the hydrogen bonds which were crucial in maintaining the secondary structural elements were disrupted.